The Effect of the Think Talk Write Type Cooperative Learning Model Assisted by Kosica Media on the Science Learning Outcomes of Grade IV Students of Balfai Kupang Tengah State Elementary School - Ndedo, Veronika; Nitte, Yulsy Marselina; Nahak, Kristina E. Noya (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Science learning aims to make students understand science concepts, have process skills, have an interest in studying the environment and be able to apply science concepts in daily life. However, there are still many students who do not understand the material and have not reached the KKM score. This can happen because the learning model used is still conventional and the use of learning media is not effective. Therefore, the researcher uses a think talk write type cooperative learning model assisted by KOSICA media to be able to improve science learning outcomes. The purpose of the study was to determine the effect of the think talk write (TTW) type cooperative learning model assisted by KOSICA media on the learning outcomes of science students in grade IV of Balfai Kupang Tengah State Elementary School. This type of research uses a Quasi experimental design in the form of a nonequivalent control group design, with a sample of 53 students and data collection techniques using observation and multiple-choice test questions. The data was analyzed using hypothesis tests and t-tests. The results of the study showed that the average post test of the experimental class and the control class. The results of this study show that the average post test of the experimental class and the control class using the hypothesis test is 85.37 > 60.77 with a difference of 24.6. The value of sig. (2-tailed) t-test for equality of means of o,ooo < 0.05 meaning Ha is accepted and HO is rejected. So it can be concluded that there is a significant influence of the use of the think talk write (TTW) type cooperative learning model assisted by KOSICA media on the learning outcomes of science students in grade IV of SD Negeri Balfai Kupang Tengah.